PENGARUH STRATEGI PROMOSI MELALUI MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN AKSESORIS HANDPHONE YANG DIMEDIASI WORD OF MOUTH (Studi pada Konsumen Bima Aksesoris Handphone di Kota Denpasar) - I Wayan Darmada; Anak Agung Putu Agung; Ni Putu Cempaka Dharmadewi Atmaja (EMAS, 2022)
The company's success in influencing consumers in purchasing decisions is strongly supported through efforts to build communication to consumers by building brands to consumers with marketing strategies, as well as innovating for new variants of a product.The purpose of this study was to determine the effect of promotional strategies through social media on purchasing decisions for mobile phone accessories and word of charge at Bima Accessories Mobile in Denpasar City. To determine the effect of word of mouth on the decision to purchase mobile phone accessories at Bima Accessories Mobile in Denpasar City. To find out whether word of mouth can mediate the effect of promotional strategies through social media on purchasing decisions for cellphone accessories at Bima Accessories Mobile in Denpasar City. The number of samples used in this study were 100 samples. Collecting data using a questionnaire. Data analysis using classical assumption test, path analysis and t test. The results of the study show that promotional strategies through social media have a positive effect on purchasing decisions for cellphone accessories in Bima, cellphone accessories in Denpasar City. Promotional strategies through social media have a positive and significant effect on word of mouth in Bima, mobile phone accessories in Denpasar City. Word of mouth has a positive and significant effect on purchasing decisions for cellphone accessories in Bima, cellphone accessories in Denpasar City. Word of mouth can partially mediate the effect of promotional strategies through social media on purchasing decisions for cellphone accessories in Bima, cellphone accessories in Denpasar City.